Very Early Severe Posttransplant Recurrent Antineutrophil Cytoplasmic Antibody-Associated Glomerulonephritis after Kidney Transplantation: Two Case Reports - Reda Laamech; Hamza Naciri-Bennani; Diane Giovannini; Johan Noble; Bénédicte Janbon; Paolo Malvezzi; Thomas Jouve; Lionel Rostaing (Case Reports in Nephrology)
Successful kidney transplantation (KTx) in patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV) has been reported with excellent patient and graft survival rates. The recurrence of AAV in transplant recipients is rare, and its mechanisms of action are not clearly known. The optimum time for KTx and the relevance of ANCA titer at the time of transplantation remain controversial. We report two cases of extremely rapid recurrent AAV after renal transplantation; both were still ANCA-positive at the time of transplantation, which led us to question the pathogenesis of ANCA antibodies in recurrence in a kidney allograft. Apheresis plus immunosuppressive therapies were ineffective in the first case and the patient became dialysis-dependent, whereas in the second case methylprednisone pulses plus rituximab infusions resulted in long-lasting remission.